The features of terminology, typology and bibliographical description of the electronic resources of educational institution - Гадецька, Зоя Митрофанівна; Одокієнко, Світлана Миколаївна (Eastern-European Journal of Enterprise Technologies, 2012)
Investigated range of problems associated with the creation and storage of electronic resources of educational institutions, namely the characteristics of their terminology ,typology and bibliographic description, etc